Quest for Identity and true self in In the Skin of a Lion and Wild Cat Falling: A Postcolonial study - Yahya, Salam Hussein; Mohammed, Ali Baram; Mani , Manimangai (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
Ondaatje and Mudrooroo use post-colonial theory as a tool to analyse and examine the life of the indigenous people and the marginalized immigrants in Australia and Canada. The characters in In the Skin of a Lion and Wild Cat Falling, after struggling with the problems of identity, try to find themselves and reconcile with their true selves in the colonial society. They want to adapt to the new life style by adopting the positive aspects of white culture. They further, retain positive aspects of their native culture and beliefs. Therefore, the paper explores how identity is reflected in the selected texts by taking postcolonial approach to the subject of the study. The study also examines the historical dimensions of post-colonialism and identity experiences, as well as their literary representations in the selected novels.